Animation videos to enhance senior high school students' motivation in learning chemistry: A learning media in inclusive schools - Ayudia, Indah; Kamaludin, Agus (Indonesian Journal of Science and Mathematics Education, 2024)
The instructional media in inclusive schools has not been fully developed inclusively in line with the potential and needs of students with disabilities. This research aims to develop inclusive instructional animation videos on chemical bonding to enhance the learning motivation of tenth-grade senior high school students. This study adopts a research and development (R and D) approach using the ADDIE development model. Research instruments utilized include quality assessment sheets and student responses. Evaluation results from subject matter experts, media experts, reviewers, and student responses indicate that the video is highly effective and well-received, with a high percentage of perceived appropriateness. Consequently, this video is deemed suitable as an alternative instructional medium in inclusive classrooms, supporting students' understanding of chemical bonding and enhancing learning motivation, especially for students with disabilities. Additionally, this research highlights the potential of utilizing Artificial Intelligence (AI) in developing inclusive instructional media.